Epidemiological and etiological features of salmonellosis in Zaporozhye region - Praise, Oluae; Furyk, E. A.; Фурик, Олена Олександрівна (Запорізький державний медичний університет, 2015)
Currently, salmonellosis remains not only one of the most important epidemiological problems, but is becoming increasingly important due to the environmental and epidemiological disadvantage in many regions of Ukraine. The aim of the investigation - to study epidemiological and etiological characteristics of salmonellosis in Zaporozhye region.